The Effects of Access to Credit on Productivity: Separating Technological Changes from Changes in Technical Efficiency - Nusrat Abedin Jimi; Plamen Nikolov; Mohammad Abdul Malek; Subal C. Kumbhakar (Institute of Labor Economics (IZA), 2019)
Improving productivity among microenterprises is important, especially in low-income countries where market imperfections are pervasive, and resources are scarce. Relaxing credit constraints can increase the productivity of microenterprises. Using a field experiment involving agricultural microenterprises in Bangladesh, we estimated the impact of access to credit on the overall productivity of rice farmers and disentangled the total effect into technological change (frontier shift) and technical efficiency changes. We found that relative to the baseline rice output per decimal, access to credit resulted in, on average, approximately a 14 percent increase in yield, holding all other inputs constant. After decomposing the total effect into the frontier shift and efficiency improvement, we found that, on average, around 11 percent of the increase in output came from changes in technology, or frontier shift, while the remaining 3 percent was attributed to improvements in technical efficiency. The efficiency gain was higher for modern hybrid rice varieties, and almost zero for traditional rice varieties. Within the treatment group, the effect was greater among pure tenant and mixed-tenant microenterprise households compared with microenterprises that only cultivated their own land.
Keywords: E22; H81; Q12; D2; O12; O16; 330; field experiment; microfinance; credit; efficiency; productivity; farmers; South Asia